Applying Halstead's Metric to Oberon Language - Fawaz Ahmed Masoud (Sultan Qaboos University Journal for Science, 1999)
Oberon is a small, simple and difficult programming language. The guiding principle of Oberon was a quote from Albert Einstein: "Make it as simple as possible, but not simpler". Oberon language is based on few fundamental concepts that are easy to understand and use. It supports two programming paradigms: the procedural paradigm, and the object-oriented paradigm This paper provides the application of Halstead's software science theory to Oberon programs. Applying Halstead's metric to the Oberon language has provided the analysis and measurements for module and within module maintenance complexity of programs written in Oberon. This type of analysis provides a manager or programmer with enough information about the maintenance complexity of the Oberon programs. So they can be aware of how much effort they need to maintain a certain Oberon program. The maintenance complexity of the programs written in Oberon or any other language is based on counting the number of operators and operands within the statements of the tested program. The counting process is accomplished by a program written in C language- Results are obtained, analyzed, and discussed in detail.